The UN Secretariat : a brief history (1945-2006) - Thant Myint-U.; Scott, Amy (Amy Enid); International Peace Academy (New York : International Peace Academy, 2007)
"The UN Secretariat: A Brief History aims to provide a concise history of the Secretariat as a much-needed background for more informed debate about this under-researched, poorly understood, yet critically important part of the UN system."--Book Jacket
Imagining the Secretariat -- Trygve Lie -- Dag Hammarskjold -- U Thant -- Kurt Waldheim -- Javier Perez de Cuellar -- Boutros Boutros-Ghali -- Kofi Annan.
Includes bibliographical references (p. 145-154).
Keywords: United Nations. -- Secretariat; United Nations. -- Secretariat -- History; United Nations. -- Secretary-General -- History -- 20th century; International relations -- 20th century; International cooperation -- 20th century